Clients' experience and satisfaction of utilizing healthcare services in a community based health insurance program in Bangladesh - Sarker, AR; Sultana, M; Ahmed, S; Mahumud, RA; Morton, A; Khan, JAM (MDPI, 2018)
Background: Community-based health insurance is recognized as a promising tool for health system improvement for low-income people that improves the health status of enrolees and enhances productivity and labor supply. The experience and opinion of the clients who utilized health services through the insurance scheme are important for improving healthcare services, shaping health policies and providing feedback on the quality, availability, and responsiveness of healthcare services. However, studies focusing on clients’ satisfaction provided by the health insurance scheme are still limited globally. Objective: To address this knowledge gap, this current study attempted to measure the degree of clients’ satisfaction towards healthcare services and insurance scheme, based on their experience of health care which will serve the future reference point to implement potential quality improvement initiatives of community-based health insurance program. Methods: A cross-sectional household survey was conducted within the catchment area of a community-based health insurance pilot program named Labor Association for Social Protection (LASP) during April–June 2014 to compare the evaluation of healthcare services provided by LASP scheme. In the descriptive analyses, the characteristics of the study participants were presented regarding frequency and the percentages with 95% confidence interval. Spearman correlation analysis was conducted between the satisfaction score of each indicator and overall satisfaction score; multivariate linear regression analysis was used to identify the factors associated with overall health scheme satisfaction. Results: The overall satisfaction mean score was 4.17 ± 0.04 (95% CI: 4.08–4.26) out of 5.00. The most satisfied domains were related to the diagnostic services (4.46 ± 0.98), explanation about the prescribed medicine (4.23 ± 0.81), the surrounding environment of healthcare facility (4.21 ± 0.70) and the behavior of health personnel toward clients (4.18 ± 0.73). Conclusions: Our study observed that the overall satisfaction level towards health services is quite favorable, but satisfaction scores can still be improved. These findings could contribute towards developing and designing the healthcare services packages of community-based health scheme which is in line with the health care financing strategy of Bangladesh as well as the recommendation of the World Health Organization for developing social health insurance as part of path to Universal Health Coverage.